गुजराती साहित्य का इतिहास - Jayantkrishna Harikrishna Dave (Uttar Pradesh Hindi Sansthan Lucknow, 2010)
The book Gujarati Sahitya Ka Itihas is about the history of Gujarati literature.
Gujarati Sahitya Ka Itihas
Keywords: Gujarati; गुजराती साहित्य का इतिहास; Gujarati Sahitya Ka Itihas; Literature; Gujarati; Hindi